Determinants of parental hesitancy to vaccinate their children against COVID-19 in China. (3rd October 2021) - Zhang, Mei-Xian; Lin, Xiao-Qing; Chen, Yan; Tung, Tao-Hsin; Zhu, Jian-Sheng
ABSTRACT: Vaccine hesitancy seriously hinders herd immunity. We explored the determinants of parental hesitancy to vaccinate children against Coronavirus Disease 2019 (COVID-19) in China. A population-based self-administered online questionnaire evaluating parental hesitancy in vaccinating their children against COVID-19 was conducted in Taizhou, China. Of the 2463 parents who received the invitation, 1788 (72.6%) responded to the survey. Of the repondents, 52.5% were hesitant. Mothers exhibited a greater proportion of vaccine hesitancy than fathers did (57.5% vs. 41.7%, P < 0.001). Multiple logistic regression analysis indicated that parents with children under 18 years of age (OR = 0.94, 95%CI: 0.90–0.99), lower knowledge scores about COVID-19 vaccination (Q1: OR = 1.92, 95%CI: 1.37–2.69; Q2: OR = 1.51, 95%CI: 1.10–2.08), lower awareness of the permission of vaccinating children (OR = 1.74, 95%CI: 1.36–2.23) and hesitancy to inoculate themselves (OR = 8.18, 95%CI: 6.48–10.33) were associated with parental hesitancy to inoculate their children. Results also revealed the disparity between fathers and mothers regarding associated factors. This study found that a substantial proportion of parents reported being hesitant to vaccinate children against COVID-19, implying the necessity of comprehensive assessment and health education programs for vaccination systems in China.